Survival and Long Transport Time of Freshwater Lobster (Cherax quadricarinatus) - Djaini, Siti Khairunnisa; Hasim, Hasim; Ahmad, Indra G (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This research aims to determine the use of rice straw as a packaging medium for the survival, growth, induction, and sedation of lobster seeds transported for 6, 9, and 12 hours using the Completely Randomized Design (CRD) method. The research preparation includes preparing the maintenance medium, filling medium, and test animals (adaptation for 7 days after arrival and fasting for 24 hours). The main research involves acclimating lobster seeds using temperature manipulation for approximately 5 minutes, with transport media temperatures ranging from 10º to 12º, and then maintaining them for 28 days. The research results indicate survival, growth, induction, and sedation time differences. The fastest induction time occurred in the treatment with a 9-hour transport duration, lasting 4.14 minutes. The fastest sedation time occurred in the 6-hour transport duration, lasting 1.56 minutes. Post-transport survival is highest after 6 hours and 9 hours of treatment, which is 95%. The best post-maintenance survival is found after 6 hours of transportation, at 91%, while the treatments at 9 and 12 hours yield 86% and 76% results, respectively. This research indicates that straw can be utilized as a filling medium for up to 12 hours